Social Isolation An Interdisciplinary View - Morese, Rosalba; Palermo, Sara; Fiorella, Raffaella (IntechOpen, 2020)
This book focuses on an increasingly current phenomenon in various countries around the world. It offers an interdisciplinary point of view with a broad and, at the same time, in-depth vision of the various aspects that can contribute to better understanding social isolation. The authors, who represent different disciplines and belong to different countries of the world, offer high-profile scientific contributions with new perspectives in the field of social security thanks to the originality of their ideas, theories, research, scientific results and suggestions. Understanding all this opens up new horizons towards the new frontiers of knowledge. "I go out. You want to come? The insulation would be too heavy; desperate and crazy on the deserted streets. To demand a destiny."(Sylvia Plath)